Quantitative and sensitive detection of alpha fetoprotein in serum by a plasmonic sensor - Xiong Yang; Hu Huatian; Zhang Tianzhu; Xu Yuhao; Gao Fei; Chen Wen; Zheng Guangchao; Zhang Shunping; Xu Hongxing (Nanophotonics)
Quantitative molecular detection based on surface-enhanced Raman spectroscopy (SERS) is still a great challenge because of the highly nonuniform distribution of the SERS hot spots and the nondeterministic spatial and spectral overlap of the analyte with the hot spot. Here, we report a nanoparticle-on-mirror plasmonic sensor excited by surface plasmon polaritons for quantitative SERS detection of alpha fetoprotein in serum with ultrahigh sensitivity. The uniform gaps between the nanoparticles and gold film and the alignment of the gap modes relative to the excitation electric field endow this substrate with a uniform and strong SERS enhancement. The limit of detection reaches 1.45 fM, 697 times higher than that under normal excitation and 7800 times higher than a commercial enzyme-linked immunosorbent assay kit. This approach offers a potential solution to overcome the bottleneck in the field of SERS-based biosensing.